Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd007007.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Screening women for intimate partner violence in healthcare settings

Abstract: Screening is likely to increase identification rates but rates of referral to support agencies are low and as yet we know little about the proportions of false measurement (negatives or positives). Screening does not appear to cause harm, but only one study examined this outcome. As there is an absence of evidence of long-term benefit for women, there is insufficient evidence to justify universal screening in healthcare settings. Studies comparing screening versus case finding (with or without advocacy or ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
120
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 93 publications
0
120
1
Order By: Relevance
“…Our findings may help inform the refinement of these comprehensive assessment tools to enhance their accuracy in detecting both abuse and mental health problems. Given evidence from a recent Cochrane review that screening alone does not increase referral or linkage to healthcare services [66], future research should also develop and evaluate the effectiveness and feasibility of integrated processes that link abuse assessment to comprehensive referral and service provision [67]. An additional policy implication is the need to advocate for an ongoing national survey of women's maternity experiences in Canada in order to enable examination of changes in risk factors for abuse over time and other important variables not available in administrative databases.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings may help inform the refinement of these comprehensive assessment tools to enhance their accuracy in detecting both abuse and mental health problems. Given evidence from a recent Cochrane review that screening alone does not increase referral or linkage to healthcare services [66], future research should also develop and evaluate the effectiveness and feasibility of integrated processes that link abuse assessment to comprehensive referral and service provision [67]. An additional policy implication is the need to advocate for an ongoing national survey of women's maternity experiences in Canada in order to enable examination of changes in risk factors for abuse over time and other important variables not available in administrative databases.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Research indicates that screening and counseling for IPV can identify survivors and, in some cases, increase safety, reduce abuse, and improve clinical and social outcomes. [11][12][13][14][15][16][17][18][19] Possible harms or unintended consequences of clinical assessment have been raised and considered in research trials, but thus far no evidence of such harm has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in the Journal of the American Medical Association found that women, who reported experiencing domestic abuse, had an associated higher lifetime prevalence of mental health disorders, dysfunction and disability. The study pointed to the sad fact that violence against women is a major public health concern, contributing to high levels of illness and death worldwide (Taft, 2013). Domestic spousal violence against women has far-reaching mental health implications.…”
Section: Psycho-social Correlates Of Domestic Violencementioning
confidence: 99%